2016
DOI: 10.3928/01477447-20160509-11
|View full text |Cite
|
Sign up to set email alerts
|

TKA for Posttraumatic Osteoarthritis Is More Complex and Needs More Surgical Resources

Abstract: The purpose of this study was to evaluate the surgical effort of total knee arthroplasty (TKA) for posttraumatic osteoarthritis (PTOA) compared with primary osteoarthritis (OA). A total of 1841 TKAs were analyzed, including 170 patients with PTOA, that resulted from soft tissue trauma in 83 patients and fractures in 87 patients. Results showed that patients were significantly younger at the time of surgery in the posttraumatic group (62 vs 71 years; P<.001). Furthermore, fracture was associated with 3.7 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…J. Dexel et al demonstrated that patients with PTOA were significantly younger at the time of surgery than those with primary OA (62 vs. 71 years, p< 0.001). In addition, operative time was significantly longer for both of the PTOA group compared with primary OA (p<0.001) [6]. This study was similar to the previous study [6] to both ages when performed TKA (56.5 vs. 63.8 years, p<0.0001), including the [17] showed the improvement of knee score from 51 to 80 degrees and knee range of motion (ROM) from 87 to 105 degrees, preoperative and postoperative, respectively in TKA with the previous history of open reduction and internal fixation of fractures of the tibial plateau.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…J. Dexel et al demonstrated that patients with PTOA were significantly younger at the time of surgery than those with primary OA (62 vs. 71 years, p< 0.001). In addition, operative time was significantly longer for both of the PTOA group compared with primary OA (p<0.001) [6]. This study was similar to the previous study [6] to both ages when performed TKA (56.5 vs. 63.8 years, p<0.0001), including the [17] showed the improvement of knee score from 51 to 80 degrees and knee range of motion (ROM) from 87 to 105 degrees, preoperative and postoperative, respectively in TKA with the previous history of open reduction and internal fixation of fractures of the tibial plateau.…”
Section: Discussionmentioning
confidence: 96%
“…Malunion, malalignment, intra-articular osseous defects, retained internal fixation devices, and compromised soft tissues may affect the outcome of total knee replacement (TKR) [1]. On average, patients affected by posttraumatic OA were approximately 10 years younger than those affected by primary knee osteoarthritis of the knee (Primary knee OA) [5,6]. Additionally, tibial plateau fracture fixation, in older patients, is more likely to require TKR [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, implementation of a TKA in patients with PTOA and limb deformity is technically challenging. Extended operation time and implant systems with higher constraint and modular options are often required. Patients undergoing a TKA for PTOA often have increased rates of revision, postoperative infection, additional procedures, and complications compared with patients undergoing a TKA for primary osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Traumatic injuries of the joint-related soft tissue, intra-articular fractures and direct cartilage impact were found to represent a crucial initiator of PTOA pathogenesis. Studies have been shown that patients suffering from PTOA are predominantly active in sports and considerably younger than the average OA patients [80,81]. Due to the mechanical impact, the ECM and embedded chondrocytes are exposed to a supraphysiological compression, causing immediate necrosis of cells [82,83].…”
Section: Pathogenesis Of Posttraumatic Osteoarthritis: Inflammation mentioning
confidence: 99%
“…Due to the still limited lifespan of the prosthetic devices and an increased risk for a revision surgery in younger patients [167], arthroplasty is often not appropriate for PTOA patients, which have an approximately 10-year earlier need for joint replacement as compared to other OA patients [80], emphasizing the urgent need for novel treatment strategies. Despite of the growing trend in regenerative medicine, including cell-based approaches, such as autologous-chondrocyte implantation (ACI) [168], injections of MSC or MCS-derived exosomes [169,170], as well as tissue engineering, combining cells, biomimetic matrices and bioactive components [171][172][173][174], this review will primarily focus on current pharmacological approaches allowing modulation of chondrocyte's behavior and fate.…”
Section: General Therapeutic Approaches In Oamentioning
confidence: 99%